THE INFLUENCE OF PERCEIVED BENEFITS AND TRUST ON INTEREST IN USING E-WALLET DANA IN KUPANG CITY - Bessie, Juita Lubrina Domina; Moenardy, Khalid K.; Benggu, Marlin (Universitas Nusa Cendana, 2025)
This research was conducted on DANA e-wallet users in Kupang City. This study aims to determine and analyze, both partially and simultaneously, the effect of perceived usefulness and trust on intention to use the e-wallet DANA in Kupang City. This study uses perceived usefulness and trust as independent variables and usage intention as the dependent variable. The number of samples was 100 respondents, with the sampling technique used being purposive sampling. Data collection was carried out using questionnaires, interviews, and literature studies. The data analysis technique used is quantitative descriptive analysis, multiple linear regression analysis, and hypothesis testing through the t-test, F-test, and analysis of the coefficient of determination (R²) using the SPSS 23 application. The results of the descriptive analysis show that overall respondents gave a very good perception assessment of perceived usefulness and trust. The results of the t-test and F-test show that partially perceived usefulness and trust have a significant effect on intention to use. Based on the adjusted R² value, the contribution of the perceived usefulness and trust variables to intention to use is 68.5%. While the remaining 31.5% of the Usage Intention variable is influenced by other variables not discussed in this study, such as risk perception, service features, and level of understanding. For this reason, it is suggested that further researchers can further examine variables outside of this study that can influence intention to use, and not only on DANA e-wallet but also on other types of e-wallets, such as OVO, Gopay, and Shopee Pay. Keywords: Perceived Benefits; Trust; Intention to Use